Level of selected toxic elements in meat, liver, tallow and bone marrow of young semi-domesticated reindeer (Rangifer tarandus tarandus L.) from Northern Norway - Hassan, Ammar Ali; Rylander, Charlotta; Brustad, Magritt; Sandanger, Torkjel Manning (International Journal of Circumpolar Health, 2012)
Objectives. To gain knowledge on toxic elements in semi-domesticated reindeer and their distribution in meat, liver, tallow and bone marrow. The correlations between concentrations in meat and liver, as well as the use of the latter as an indicator for toxic elements in meat, were also investigated. Study design. Cross-sectional study on population of semi-domesticated reindeer from 2 northern Norwegian counties (Finnmark and Nordland). Methods. Semi-domesticated reindeer carcasses (n 31) were randomly selected, from which meat, liver, tallow and bone marrow samples were collected. Selected toxic elements (cadmium, lead, arsenic, nickel and vanadium) were studied. Results. Liver was the organ with the highest level of all elements except for nickel, which was highest in bone marrow. Meat had the lowest levels, whereas levels in tallow and bone marrow were between those of meat and liver. Concentrations of cadmium, lead and arsenic were significantly different (pB0.05) between meat and liver, while only arsenic and cadmium were significantly correlated in meat (rs 0.71, pB0.01) and liver (rs 0.72, pB0.01). The cadmium level exceeded the European Commission’s (EC) maximum level set for bovine meat and liver in 52% of the liver samples (n 29). Nevertheless, the estimated monthly cadmium intake from liver of 2.29 mg/kg body weight was well below the provisional tolerable monthly intake of 25 mg/kg body weight set by the FAO/WHO Joint Expert Committee on Food Additives. Conclusions. Based on the measured levels and their relation to the maximum level and to the provisional tolerable weekly/monthly intake limits, it could be inferred that consumption of reindeer meat is not associated with any health risk related to the studied toxic elements for consumers.